Effect of surface sterilizing agents on establishment of axenic culture in kinnow mandarin (Citrus deliciosa) (Indian Journal of Arid Horticulture, 2025)
The surface sterilization is the most important step prior to initiate tissue culture and can become a critical point in establishment of certain species particularly when the explants was derived from field grown woody perennial plants. Kinnow mandarin (Citrus deliciosa) is a cross, between the king sweet orange (Citrus nobilis) and Willow leaf mandarin (C: deliciosa) developed in California by H.B. Frost. Kinnow fruits have a great therapeutic value due to favourable ratio of K and Na. Kinnow fruits are not only delicious and refreshing but also possess great nutritive value. It contains 10-12% carbohydrate, 0.6-0.8% protein, 0.9-1.1% vitamin A, 0.45-0.55% vitamin C, 0.01- 0.02% thiamine, 0.002 -0.003% riboflavin, 0.25-0.35% calcium, 0.18-0.25% magnesium and 0.028-0.034% iron.
Keywords: mandarin; sterilization; perennial plants; therapeutic